Correlates of Human Development amongst Adolescents in Malaysian National Religious Secondary Schools - Mohamed, Othman; Md. Aroff, Abd. Rahman; Zakaria, Abdul Aziz; Yaacob, Noran Fauziah (Universiti Putra Malaysia Press, 1994)
The study investigated the correlates of human development among National Religious Secondary School students in Malaysia, consistent with the Erikson (1968) epigenesis of identity approach and the Chickering (1972) vectors of adolescent development. The research design incorporated a regression analysis model with human development as the dependent variable with eight predictors, i.e. the family, the school environment, sense of purpose, self, society, academic, co-curriculum,and the hostel environment. The regression value was significant, F(8, 1099) = 18.475, P < .05, with R2 of .119 indicating that the eight predictors explained an influence of 11.9% towards human development. The contribution was moderate. Generally, the respondents were aware of their sense of purpose with regards to what they intended to achieve. Moreover, the National Religious Secondary School students have moved towards self autonomy in relation to an awareness of human development.